Integrating E-Business with Marketing: Strategies for Sustainable Growth in the Digital Era - Maulida, Vida Wahda; Mariana, Soneta Dina; Akbar, Muhammad Fadil; Suri, Brigita Sheren Jessica; Redjeki, Finny (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The integration of e-business into marketing strategies has transformed how Small and Medium Enterprises (SMEs) reach and engage with their customers. This study investigates the impact of e-business tools on the marketing performance of SMEs, focusing on digital advertising, customer relationship management (CRM), and social media utilization. Using a qualitative approach, interviews were conducted with 20 SME owners who have successfully implemented e-business. Findings reveal that adopting e-business significantly improves market reach, customer retention, and overall marketing efficiency. The study recommends continuous digital skill development and leveraging data analytics to optimize marketing outcomes.